Sistem Pendukung Keputusan Penentuan Calon Penerima Beasiswa BBP-PPA Menggunakan Metode AHP-PROMETHEE I Studi Kasus : FILKOM Universitas Brawijaya - Nining Nahdiah Satriani; Imam Cholissodin; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Scholarship is financial assistance given to individuals for the purpose of sustainability education. Every year, Universitas Brawijaya offers scholarships to underprivileged students, one of them i.e. BBP-PPA scholarships. Scholarships should be given to appropriate candidates so that the objectives of the program can be achieved on target. Selection of scholarship awardee includes several criteria, such as parental income, parental expenses, GPA, and parental dependents. However, complaints often arise from other students when the awardee is not eligible to get a scholarship. Morevover the selection still done manually so that the process of determining the awardees tend to take a long time.Analytical Hierarchy Process-Preference Ranking For Organizatiom's Evaluation I (AHP-PROMETHEE I) is one of the methods that combine the method of AHP and PROMETHEE I. The results of the tests to determine the effect of the matrix comparison on the accuracy of the system. The results showed the accuracy of 73% for calculations using leaving flow, and 93% calculation using entering flow data from experts. Based on the accuracy can be said that the method of AHP-PROMETHEE I has a good performance in the determination of the candidates BBP-PPA scholarship.